The role of re-transurethral resection of bladder tumor in patients with TaHG non muscle invasive bladder cancer - Scilipoti, Pietro; Moschini, Marco; de Angelis, Mario; Afferi, Luca; Lonati, Chiara; Longoni, Mattia; Tremolada, Giovanni; Zaurito, Paolo; Viti, Alessandro; Santangelo, Alfonso; Pichler, Renate; Necchi, Andrea; et al. (World journal of urology, 2024)
PURPOSE: There is lack of evidence regarding the indication for re-transurethral resection of bladder tumor (reTURBT) for Ta high grade (HG) non-muscle invasive bladder cancer (NMIBC). This study aims to evaluate the oncological outcomes of patients with TaHG NMIBC to determine the benefit from performing reTURBT. METHODS: We relied on a multicenter cohort of 317 TaHG NMIBC from 12 centers who underwent TURBT and a subsequent complete Bacillus Calmette-Guérin induction from 2009 to 2021. Kaplan Meier analyses estimated recurrence free survival (RFS) and progression free survival (PFS) according to reTURBT. Sub-analyses evaluated PFS in patients with multiple risk factors indicating necessity for reTURBT according to international guidelines (multifocality, size > 3 cm, recurrent cancer, carcinoma in situ, lymph vascular invasion, histological variant, incomplete and absence of muscle layer at index TURBT). Multivariable cox-regression analysis predicted recurrence and progression. RESULTS: Of the 317 patients, 123 (39%) underwent reTURBT, while 194 (61%) did not. Residual disease was detected in 46% of cases, with a 3.2% upstaging rate. Median follow-up was 30 months. The 3-year RFS was higher in patients who underwent reTURBT (79% vs. 58%, p < 0.001), but no significant difference was observed in PFS. ReTURBT reduced the risk of recurrence [multivariable hazard ratio: 0.45, 95% Confidence interval (CI) 0.29-0.71]. Among patients who did not undergo reTURBT, those with ≥ 2 risk factors had lower 3-year PFS (73% vs. 92%, p < 0.001) than those with 0-1 risk factor, whereas no difference in 3-year PFS was observed in patients who underwent reTURBT regardless of the number of risk factors (85% vs. 87%, p = 0.8). CONCLUSION: ReTURBT demonstrated efficacy in reducing recurrence among patients with TaHG NMIBC, yet its impact on progression remained uncertain. Our study underscores the importance of adhering to current international guidelines, particularly for patients with multiple risk factors indicating necessity for reTURBT.
Keywords: Transurethral Resection of Bladder; mužské pohlaví; Retrospective Studies; Male; senioři; výsledek terapie; retrospektivní studie; uretra; stupeň nádoru; Humans; Female; Ta high grade; Urethra; lokální recidiva nádoru; nádory močového měchýře; lidé; cystektomie; Middle Aged; ženské pohlaví; lidé středního věku; Neoplasm Invasiveness; reoperace; Non muscle invasive bladder cancer; Cystectomy; Progression; Re-transurethral resection of bladder tumor; Treatment Outcome; Recurrence; Urinary Bladder Neoplasms; Neoplasm Grading; Reoperation; invazivní růst nádoru; transuretrální resekce močového měchýře; Neoplasm Recurrence, Local; Aged